2017
DOI: 10.1037/hea0000508
|View full text |Cite
|
Sign up to set email alerts
|

An initial application of a biopsychosocial framework to predict posttraumatic stress following pediatric injury.

Abstract: Objectives Each year millions of children suffer from unintentional injuries resulting in poor emotional and physical health. This study examined selected bio-psycho-social factors (child heart rate, peri-trauma appraisals, early coping, trauma history) to elucidate their roles in promoting emotional recovery following injury. The study evaluated specific hypotheses that threat appraisals (global and trauma-specific) and coping would predict subsequent posttraumatic stress symptoms (PTSS), that coping would me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…cognitive restructuring, seeking social support, problem-solving), while a minority was more avoidance-oriented ( Aldridge and Roesch, 2007 ; Roth and Cohen, 1986 ). Specifically, avoidant coping has been associated with more posttraumatic stress ( Marsac et al, 2017 ; Stallard et al, 2001 ), while approach-oriented coping has not clearly been shown to reduce the risk of posttraumatic stress ( Marsac et al, 2017 ). In clinical practice, attention could be paid to the type of coping strategy used by the child.…”
Section: Discussionmentioning
confidence: 99%
“…cognitive restructuring, seeking social support, problem-solving), while a minority was more avoidance-oriented ( Aldridge and Roesch, 2007 ; Roth and Cohen, 1986 ). Specifically, avoidant coping has been associated with more posttraumatic stress ( Marsac et al, 2017 ; Stallard et al, 2001 ), while approach-oriented coping has not clearly been shown to reduce the risk of posttraumatic stress ( Marsac et al, 2017 ). In clinical practice, attention could be paid to the type of coping strategy used by the child.…”
Section: Discussionmentioning
confidence: 99%
“…Models including biological, psychological, and social factors have been proposed to understand the development of PTSR (Marsac et al, 2017). When exposed to a lifethreatening experience, the body reacts with a cascade of acute biological stress responses.…”
Section: Models and Predictors For The Development Of Ptsrmentioning
confidence: 99%
“…Peri-traumatic risk factors such as trauma severity, perceived life threat, emotional responses, dissociation, and loss of loved ones have been demonstrated to be particularly strong predictors of PTSR (Brewin, 2005;Furr, Comer, Edmunds, & Kendall, 2010;Kahana, 2006;Ozer et al, 2003;Skogstad et al, 2014). Early psychological reactions including PTSR, elevated heart rate, lack of social support, ongoing life stressors, early maladaptive appraisals, and avoidant coping have been demonstrated as significant post-trauma factors (Bisson, 2007;Brewin, 2005;Marsac et al, 2017;Ozer et al, 2003;A. Y. Shalev et al, 2019).…”
Section: Models and Predictors For The Development Of Ptsrmentioning
confidence: 99%
“…Recently, Marsac et al (2017) hypothesized that coping and appraisals could serve as mediators of associations between early and later posttraumatic stress symptoms. This is a rare case in which the researchers provided a compelling case for the impact of the IV on hypothesized coping-related mediators.…”
mentioning
confidence: 99%